Hubungan Tingkat Religiusitas dengan Kemampuan Coping Stress Siswa di SMAN 2 Payakumbuh - Azzati Nur Laili; Budi Santosa; Fadhilla Yusri; Syawaluddin Syawaluddin (Concept: Journal of Social Humanities and Education, 2023)
This research aims to determine whether there is a relationship between the level of religiosity and a person's ability to cope with stress and to determine the magnitude of the relationship between the level of religiosity and the ability to cope with stress. This type of research is quantitative correlational research, because it aims to determine whether there is a relationship or influence between two variables. The population in this study was classes X and The samples were taken using a purposive sampling technique because there were several considerations. Data collection used a questionnaire instrument with a Likert scale. The results of the research show that based on the r_count value (Pearson Correlations), it is known that the r_count value for the relationship between the level of Religiosity (X) and the ability to Coping with Stress (Y) is r_xy of 0.479 and r_table df n-2 (60-2) 58, namely 0.254, so it can be concluded that There is a relationship between the level of religiosity and the ability to cope with stress. Because r_count or Pearson Correlations in this analysis is positive, it means the relationship between the two variables is positive. The calculation results of the coefficient of determination are 22.9%, so it can be said that the magnitude of the relationship is 22.9%, the variance in the level of religiosity is associated with the variance in students' stress coping abilities at SMAN 2 Payakumbuh.